PRESIDENTIAL THRESHOLD DALAM PEMILIHAN UMUM SERENTAK: KEMUNDURAN DEMOKRASI KONSTITUSIONAL? - Alfa Fitri (2022)
Indonesia since the 1945 Constitution which was implemented in 1999- 2002 has chosen the Presidential System in the practice of state administration. Presidential logistics system is that the President is no longer the mandate of the People's Consultative Assembly, but directly as the mandate of the people who are directly elected as a form of Democracy. The presidential threshold chosen as an effort to strengthen the Presidential system which is applied to simultaneous general elections is the choice of legislators. This study uses a normative juridical method combined with a conceptual approach and utilizes secondary qualitative data. This study conclude, first, how the implementation and influence of the Presidential Threshold in general elections simultaneously. Second, how is the constitutional view of the Presidential Threshold in the general election simultaneously